The Current Knowledge on Navigated Retinal Laser Therapy (Navilas) - Lachowicz, Ewelina; Lubiński, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Digital systems supporting laser therapy enabled the introduction of new quality navigated laser therapy for the treatment of retinal diseases. Navilas is the first and so far the only camera in the world that uses this technology and allows for standardized management. The used wavelength (577 nm yellow) is currently recommended for retinal diseases treatment. The microsecond pulse mode additionally gives the possibility of the therapy of subfoveal and peri-foveal lesions. By using the innovative technology Navilas significantly exceeds conventional laser therapy. The system offers high precision and long-lasting satisfactory therapeutic effect with an increased level of safety. Navigated retinal laser therapy was used till now in: the central retinal vein or its branches occlusion, proliferative diabetic retinopathy, diabetic macular edema, central serous chorioretinopathy, macroadenomas, retinal telangiectasias, polyploidal choroidal vasculopathy, and in case of peripheral changes. Navigated therapy has the potential possibility to replace traditional laser therapy in many retinal diseases.